Community Assistance in Managing Kitchen Waste to Become Organic Fertilizer - Hamzah, A. Hadian Pratama; Mulatsih, Listiana Sri; Zuhroh, Siti; Alfiana, Alfiana; Masdiana, Masdiana; Nurhasanah, Nurhasanah (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Researchers, together with the manager of the Asri Garbage Bank, formed a collaboration to socialize the habit of selecting waste. This kitchen waste will be made into compost and sold to the surrounding community. This activity aims to familiarize the people in Green Petunia Housing with managing waste to reduce the amount of garbage. The method used in this service is the PAR (Participatory Action Research) method, with stages through training, account creation practices, and mentoring. The training is carried out in three phases: preparation, implementation, and evaluation. The results obtained from this activity are that people are increasingly aware of the importance of selecting waste and getting used to processing waste to reduce the amount of plastic waste around them.